Constitutionality and Legal Reconstruction of Social Security System from Pancasila and Constitutional Perspectives - Wibisono, M. Iqbal (Jurnal Pembaharuan Hukum, 2025)
This study aims to evaluate the constitutionality of the social security system in Indonesia, especially the National Social Security System (Sistem Jaminan Sosial Nasional/SJSN) and the Social Security Administering Body (Badan Penyelenggara Jaminan Sosial/BPJS), in order to guarantee the basic rights of citizens in accordance with the 1945 Constitution. This study uses a normative legal approach by analyzing existing regulations and the Constitutional Court's decision regarding the constitutionality of SJSN and BPJS. The findings show that SJSN and BPJS, which are regulated in Law Number 40/2004 and Law Number 24/2011, are constitutional according to the Constitutional Court. However, in practice, there is a discrepancy between the implementation of the system and the mandate of the 1945 Constitution which requires the state to provide fair social security for all people, especially in terms of coverage for vulnerable groups and informal workers. Its implementation still faces obstacles in terms of effectiveness, affordability, and equity. This study suggests the need for reconstruction of the social security system with a more responsive approach to the real needs of the community, as well as strengthening supervision to be in line with constitutional principles and Pancasila values.